1957
DOI: 10.1017/s0305004100032151
|View full text |Cite
|
Sign up to set email alerts
|

A relativistic form of Boltzmann's transport equation in the absence of collisions

Abstract: With the neglect of collisions, a relativistic form of Boltzmann's transport equation is derived and its invariance under a Lorentz transformation is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1960
1960
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…As was shown by TAuB [8], CLEMMOW and WILLSO~ [9], and LIr~nART [10], the collision-free Boltzmann equation can be put in certain relativistic noncovariant forms, while Ks.N-ITI GOTO [11] gave a covariant form of the relativistic Boltzmann equation. In 1965, ABONYI [12] showed that the forms proposed by TAUB, CLEMMOW and WILLSON and LINnART are equivalent, the form given by KE~-ITI Goro being valid only for the "four-power free" forces.…”
Section: Lntroductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As was shown by TAuB [8], CLEMMOW and WILLSO~ [9], and LIr~nART [10], the collision-free Boltzmann equation can be put in certain relativistic noncovariant forms, while Ks.N-ITI GOTO [11] gave a covariant form of the relativistic Boltzmann equation. In 1965, ABONYI [12] showed that the forms proposed by TAUB, CLEMMOW and WILLSON and LINnART are equivalent, the form given by KE~-ITI Goro being valid only for the "four-power free" forces.…”
Section: Lntroductionmentioning
confidence: 98%
“…If the microscopic velocity four rector uf is defined by Ur = <ttr > q Wr ' (9) where <Ur> iS the macroscopic (mean) velocity four vector, and w r the deviation from (Ur>, and observe that (wr> = 0, then we get successively: …”
Section: Galilean Coordinatesmentioning
confidence: 99%
“…In general, the particle distribution function / depends on the variables t, x and ijr. It is convenient to present the Vlasov relativistic kinetic equation (Clemmow & Willson 1956) in those variables in the form…”
Section: Gyrokinetics Of Resonant Particles 179mentioning
confidence: 99%
“…Moreover relativisitic effects have not been taken into account; these can be very important in resonant conditions because the difference between frequencies at cyclotron resonances is very sensitive to relativisitic changing of the gyrofrequency of particles. In addition, relativistic effects can strongly change the dispersion relation for waves (Clemmow & Willson 1956). A relativistic kinetic theory in the particular case of electron-cyclotron resonance has been developed by Bernstein & Baxter (1981), but is not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Work based on approximations of the equilibrium distribution function with and without streaming cannot be applied to fusion reaction chambers, relativistic electron beam experiments necessitating the fusion of nuclei, etc. (Clemmow & Willson 1956;Kursunoglu 1961;Buti 1963aButi , b, 1972. Misra (1975) derived dispersion relations for transverse and longitudinal waves propagating in a Vlasov plasma valid for relativistic and nonrelativistic temperatures for one-component electron plasma.…”
Section: Introductionmentioning
confidence: 99%